General Practitioners' Experiences of Digital Written Patient Dialogues: A Pilot Study Using a Mixed Method - Anders Johansson; Monica Larsson; Bodil Ivarsson (SAGE Publishing, 2020)
Background: The path between patients and health care providers has adopted new advanced information technologies. However, opinions vary about the digital care meeting. Physicians have expressed concerns about increased workload, changes in working methods, and information security. Purpose: To explore physicians' experiences and satisfaction of digital primary health care. Method: A convergent mixed method was used. First, participants completed a quantitative questionnaire survey with fixed response options described as index values (IV, 0-1.0), supplemented with a 10-point Likert-type scale, estimating satisfaction. Second, a qualitative interview used critical incident technique (CIT) to offer more complete context. Data were collected during 2 months in 2019; 6 general practitioners (GPs) participated. Results: The GPs described good experiences of the concept (IV 0.65), corresponding to a median satisfaction value of 6.5 (interquartile range 5-9,). CIT emerged into 2 main areas; "Hovering between traditional and digital primary health care" and "Using active strategies to handle the digital care system." GPs experienced that the concept offered a good flow, an asynchronous working approach was used. GPs also stated present chat design was a good complement to traditional forms of primary health care, and the benefits of being able to read patients' self-described history were considered a significant patient safety factor. However, the GPs felt that a predetermined symptom list were not suitable for all patients. Conclusion: Study results suggest the present design using digital written patient dialogues complements traditional primary healthcare. GPs described satisfaction and expressed good experiences of the concept, although further development of the design is needed.